2008
DOI: 10.1007/s10484-007-9046-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Portable Biofeedback Device into Clinical Practice for Patients with Anxiety Disorders: Results of a Pilot Study

Abstract: This study examined the effectiveness of a portable Respiratory Sinus Arrhythmia (RSA) biofeedback device as an adjunct to CBT in persons with anxiety disorders and other disorders associated with autonomic dysfunction attending outpatient treatment. Participants were 24 individuals attending outpatient cognitive behavioral treatment for a range of anxiety disorders. Participants were assessed over a 3 week period. Outcomes included measures of anxiety (STAI-Y), sleep disturbances (PSQI), anger (STAEI), and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(88 citation statements)
references
References 31 publications
3
76
2
7
Order By: Relevance
“…MoodWings [11] is a wearable device in the shape of a butterfly, with wings that actuate in real time to a user's heart rate. This type of interaction has been shown to be more effective at reducing stress than traditional approaches found in meditation [12], thus showing promise for actuated technology in yoga practices. ''Broncomatic'' is an actuated amusement ride controlled by the riders' breath [13].…”
Section: Related Workmentioning
confidence: 99%
“…MoodWings [11] is a wearable device in the shape of a butterfly, with wings that actuate in real time to a user's heart rate. This type of interaction has been shown to be more effective at reducing stress than traditional approaches found in meditation [12], thus showing promise for actuated technology in yoga practices. ''Broncomatic'' is an actuated amusement ride controlled by the riders' breath [13].…”
Section: Related Workmentioning
confidence: 99%
“…This method is easy to use and has established efficacy in the treatment of depression 48 and anxiety disorders. 49 The reciprocity of cortico-cardiac interactions, based on cortical plasticity, provides opportunities for behavioral interventions. 50,51 Electrophysiological correlates of behavior (e.g., event-related potentials) illuminate features of cognitive top-down and bottom-up processes such as evaluation, categorization, orienting/alertness, or novelty and are sensitive to pharmacological treatments.…”
Section: Descriptive Correlational Research Approachmentioning
confidence: 99%
“…Several features such as amplitude and latency of eventrelated potentials can be linked to behavioral or cognitive dysregulation. Response inhibition paradigms combine behavioral tasks requiring motor inhibition in standardized and well-established paradigms such as Go-NoGo, 48,49 stop-signal, 53 or others with corresponding electrophysiological measures such as N200 amplitude. 54 A sensitive measure such as the inhibition-related N200 event-related potential may be able to assess subclinical changes in cognitive and behavioral regulation processes, 55 which have been suggested to be based on a supermodal inhibition-eliciting initiatior in the right inferior prefrontal cortex and, therefore, to be closely linked to cognitive adaptivity and flexibility.…”
Section: Descriptive Correlational Research Approachmentioning
confidence: 99%
“…More recent studies have reinforced the importance and effectiveness of biofeedback training programs on anxiety intervention. Reiner (2008) concluded that biofeedback may be a useful adjunct to behavioural therapies, and may be helpful to those who have difficulty adhering to and/or performing traditional relaxation therapies. Ratanasiripong, Sverduk, Prince and Hayashino (2012) conducted a study in order to investigate the impact of a biofeedback program in stress and anxiety of a nursing students group during their first clinical training.…”
Section: Introductionmentioning
confidence: 99%